THE EFFECT OF EDUCATIONAL VIDEOS ON ATTITUDES TOWARDS HPV VACCINE ADMINISTRATION TO STUDENTS OF SDN TATAH BELAYUNG BARU IN 2025 - Paujiah Paujiah; Rusmilawaty Rusmilawaty; Rita Kirana; Yuniarti Yuniarti (Universitas Muhammadiyah Ponorogo, 2026)
Based on data from the Kertak Hanyar Health Center, the vaccination coverage is only the national HPV vaccination rate has only reached 70%, leaving 25% gap that needs to be addressed. Kertak Hanyar District rank fifth among community health centers with the lowest HPV vaccination coverage, with Tatath Belayung Baru Village as the lowest-performing village, with Tatah Belayung baru Elementary School as its target. To determine the effect of educational videos on mothers attitudes towards administering HPV vaccines to students at SDN Tatah Belayung Baru in 2025. This study was a pre-experimental study with a one group pre-post test design. The sampling technique used was a total sample of 30 parents of grade 5 and 6 students. Data analysis used the wilcoxon Signed Rank Test with a significance value of 0,05. Mothers’ attitudes before the video media was given showed an average score of 58.00. After the video media was given, the average mothers’ attitude score was 88.67. There was an effect of educational videos on mothers’ attitudes toward providing HPV vaccination to students, with a p-value of 0.000. There is an effect of educational videos on mothers’ attitudes in providing HPV vaccination to students at SDN Tatah Belayung Baru in 2025. Keywords: Video, Education, Attitude and HPV Vaccine